School Efforts to Establish PAI Teacher Competence in Implementing the Independent Learning Curriculum - Syafe’i, M. Dendi; Oktaviani, Heriyah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
The Curriculum in Indonesia has undergone several changes, with the last Curriculum, K13, now changing to the current famous Curriculum, the Merdeka Learning Curriculum (Rahman et al., 2023). To understand the types of competencies needed by PAI teachers in implementing the Independent Curriculum and To find out what programs are organized by schools to improve the competence of PA teachers at SMAN 1 Jarai and Identify the challenges faced by schools in developing PAI teacher competencies in implementing the Independent Curriculum at SMAN 1 Jarai. The type of research that researchers use is qualitative research, and in this study, they use a descriptive approach to analysis. The school's efforts in shaping the competence of Islamic Religious Education (PAI) teachers in high schools are essential to ensuring high-quality teaching is relevant to student needs. Overall, the competency building of PAI teachers in high schools requires a coordinated and ongoing effort involving training, facility support, professional collaboration, periodic evaluations, and supportive leadership. With this approach, PAI teachers can be more effective in teaching, inspiring students, and supporting the development of students' character and spirituality through Islamic religious values.